PENGARUH MODAL KERJA TERHADAP PROFITABILITAS PADA KOPERASI âXâ BANDUNG - Kostini, Nenden; Dai, Ratna Meisa; Andriani, Evi (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2018)
ABSTRACTFinancial services cooperatives are classified as Non-bank Microfinance Institutions (MFIs) and become alternative funding for micro, small and medium enterprises (MSMEs). Non-bank MFIs are believed to play a strategic role in meeting the capital needs of MSMEs. However, the role of non-bank MFIs is still low so that the potential of MSME as a supporter of economic growth canât be realized. Cooperative